Patellofemoral Arthralgia, Overuse Syndromes of the Knee, and Chondromalacia Patella - Welsh, R. Peter (1985)
Patellofemoral arthralgia is a very common syndrome affecting athletes. Most often, examination fails to define true pathology. Conservative treatment, an active exercise program, and sports may be undertaken without harm to the knee. The patellofemoral arthralgia syndrome must be differentiated from true chondromalacia patella, where there is actual degeneration of the patella's articular cartilage, and from other sources of internal derangement such as meniscal disease or osteochondral lesions. Careful attention to the history of onset, and provoking activities such as climbing stairs, kneeling, and crouching, will allow the physician to recognize patellofemoral arthralgia. Other common overuse syndromes also should be looked for, and differentiated from problems due to true internal derangement.